2019
DOI: 10.1038/s41598-019-54598-w
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Visual Prognosis in Open Globe Injuries: Results of A Tertiary Referral Center in Turkey

Abstract: We aimed to analyse the clinical characteristics of OGI and evaluate the correlation between baseline ocular trauma score (OTS) and visual outcomes in cases with OGI. The charts of 257 OGI patients who had at least six months of follow-up were reviewed retrospectively. Demographics, data about the etiology, localization and size of the OGI, baseline and final best-corrected visual acuity (BCVA) were noted. At the time of approval OTS was calculated and compared with final BCVA. All analysis was performed in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
7
11
0
Order By: Relevance
“…In this study, poor presenting visual acuity is significantly associated with poor post-operative visual outcomes. This is in accordance with other studies that showed presenting VA is the most important prognostic factor in determining visual outcome [2][3][4][5]. Presence of RAPD and vitreous loss were statistically significant to predict post-operative visual outcomes in this study.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In this study, poor presenting visual acuity is significantly associated with poor post-operative visual outcomes. This is in accordance with other studies that showed presenting VA is the most important prognostic factor in determining visual outcome [2][3][4][5]. Presence of RAPD and vitreous loss were statistically significant to predict post-operative visual outcomes in this study.…”
Section: Discussionsupporting
confidence: 93%
“…This reflects the predominant involvement of men in higher-risk activities namely work or sports-related activities and motor vehicle accidents. The majority of patients were in the younger age group (less than 40 years old) which is also similar to other studies till date [ 2 - 4 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations